2015
DOI: 10.1177/0888406414565838
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Students With ASD Using Evidence-Based Practices

Abstract: Given the growing numbers of students identified with autism, educators need an understanding of evidence-based practices (EBPs) to meet these student’s individual educational goals. EBPs are defined often as instructional strategies, interventions, or teaching programs that result in consistent positive student outcomes. Educator’s use of EBPs has been shown to improve the learning outcomes of students with disabilities. It is imperative that educators understand how to select and implement such practices wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
(15 reference statements)
0
20
0
1
Order By: Relevance
“…Didactic training could help spread information but may not lead to using that information (Morrier et al, 2011 ). Training teachers to use EBPs should advance beyond didactic instruction, to emphasize practicing EBPs inside the classroom and provide feedback on their implementation (Marder and deBettencourt, 2015 ). The programs should include hands-on activities and opportunities to practice and receive feedback from an expert coach or supervisor in the use of EBPs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Didactic training could help spread information but may not lead to using that information (Morrier et al, 2011 ). Training teachers to use EBPs should advance beyond didactic instruction, to emphasize practicing EBPs inside the classroom and provide feedback on their implementation (Marder and deBettencourt, 2015 ). The programs should include hands-on activities and opportunities to practice and receive feedback from an expert coach or supervisor in the use of EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…The research has emphasized using evidence-based practices (EBPs; Odom et al, 2013 ; Wong et al, 2015 ) to meet the significant needs of students with ASD in inclusive classrooms (Marder and deBettencourt, 2015 ). Research has indicated that a teacher's use of EBPs can significantly improve the outcomes of students with ASD and the lives of their families (Cook and Odom, 2013 ; Alexander et al, 2015 ; Marder and deBettencourt, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations